Music of the Planets: An Interdisciplinary Digital Storytelling Approach in Kindergarten - Tsoura, Androniki (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2026)
This paper presents the design, implementation, and evaluation of an interdisciplinary digital storytelling project titled Music of the Planets, aimed at preschool children. Combining music, science, and digital technology, the scenario utilized Gustav Holst’s The Planets as a narrative anchor to engage children in multimodal learning experiences. Children explored planets and composed music using interactive tools. The project emphasized inquiry-based learning, digital literacy, and creative expression, while also fostering collaboration and critical thinking. Observations revealed high levels of engagement, emotional connection, and meaningful participation, highlighting the potential of digital storytelling as an effective pedagogical tool in early childhood education. Challenges related to technical resources and time investment were noted, but overall, the program demonstrated strong alignment with STEAM education principles.